The children's transfer from a group to another during the school period - Cláudia Regina Pinto Michelli (Universidade Federal de Santa Catarina, 2008)
This article refers to the process of reorganization of the groups with the children's of a group transfer to other motivated by the age group change during the school period. The process was observed in an institution of Infantile Education located in a city of the state of Santa Catarina. The analysis of that process was the central axis of a master's degree research, that looked for to understand the implications of such a change process taking as base the children's speech, the speech of their parents and of their educators. In the chosen cutting to compose the present article we present the results of the interviews that we accomplished with the children (all of them with three years age). We tried to consider the desires and the children's point of view starting from that specific experience. We understood that when hearing the child talk about your experience in relation to the transfer process, it would be possible to guide reflections on like she notices the context of the day care, as well as to promote a more attentive glance of the adult in the sense of considering the child as an active social subject that deserves to be considered in the activities that take place with him. We understood that to work just with the adult's point of view it is not enough to characterize a significant work with the children in the sense of an education that looks for the construction of the social emancipation.